HPV RNA CISH score identifies two prognostic groups in a p16 positive oropharyngeal squamous cell carcinoma population. (November 2018) - Augustin, Jérémy; Mandavit, Marion; Outh-Gauer, Sophie; Grard, Ophélie; Gasne, Cassandre; Lépine, Charles; Mirghani, Haïtham; Hans, Stéphane; Bonfils, Pierre; Denize, Thomas; Bruneval, Patrick; Bishop, Justin; et al.
Abstract HPV-related and HPV-unrelated oropharyngeal squamous cell carcinomas are two distinct entities according to the Union for International Cancer Control, with a better prognosis conferred to HPV-related oropharyngeal squamous cell carcinomas. However, variable clinical outcomes are observed among patients with p16 positive oropharyngeal squamous cell carcinoma, which is a surrogate marker of HPV infection. We aimed to investigate the prognostic value of RNA CISH against E6 and E7 transcripts (HPV RNA CISH) to predict such variability. We retrospectively included 50 histologically confirmed p16 positive oropharyngeal squamous cell carcinomas (p16 positive immunostaining was defined by a strong staining in 70% or more of tumor cells). HPV RNA CISH staining was assessed semi-quantitatively to define two scores: RNA CISH "low" and RNA CISH "high". Negative HPV RNA CISH cases were scored as RNA CISH "low". This series contained 29 RNA CISH low cases (58%) and 21 RNA CISH high cases (42%). Clinical and pathologic baseline characteristics were similar between the two groups. RNA CISH high staining was associated with a better overall survival in both univariate and multivariate analyses (p  = 0.033 andp  = 0.042, respectively). Other recorded parameters had no prognostic value. In conclusion, HPV RNA CISH might be an independent prognostic marker in p16 positive oropharyngeal squamous cell carcinomas and might help guide therapeutics.